2010
DOI: 10.5194/acp-10-3545-2010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochlorofluorocarbon and hydrofluorocarbon emissions in East Asia determined by inverse modeling

Abstract: Abstract. The emissions of three hydrochlorofluorocarbons, HCFC-22 (CHClF 2 ), HCFC-141b (CH 3 CCl 2 F) and HCFC142b (CH 3 CClF 2 ) and three hydrofluorocarbons, HFC-23 (CHF 3 ), HFC-134a (CH 2 FCF 3 ) and HFC-152a (CH 3 CHF 2 ) from four East Asian countries and the Taiwan region for the year 2008 are determined by inverse modeling. The inverse modeling is based on in-situ measurements of these halocarbons at the Japanese stations Cape Ochi-ishi and Hateruma, the Chinese station Shangdianzi and the South Kore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
147
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 128 publications
(165 citation statements)
references
References 36 publications
(71 reference statements)
16
147
2
Order By: Relevance
“…Several papers report Asian emissions of HFC-23, including those for China Stohl et al, 2010;Kim et al, 2010;Li et al, 2011;Yao et al, 2012). Recent papers by Fang et al (2014Fang et al ( , 2015 noted inconsistencies between the various bottom-up and top-down emissions estimates and provided an improved bottom-up inventory and a multi-annual top-down estimate of HFC-23 emissions for East Asia.…”
Section: Regional Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several papers report Asian emissions of HFC-23, including those for China Stohl et al, 2010;Kim et al, 2010;Li et al, 2011;Yao et al, 2012). Recent papers by Fang et al (2014Fang et al ( , 2015 noted inconsistencies between the various bottom-up and top-down emissions estimates and provided an improved bottom-up inventory and a multi-annual top-down estimate of HFC-23 emissions for East Asia.…”
Section: Regional Emissionsmentioning
confidence: 99%
“…Kim et al (2010), reported HFC-23 measurements (November 2007-December 2008 from Gosan, Jeju Island and South Korea and also estimated regional atmospheric emissions. Asian emissions of HFC-23, including those for China have been reported by Yokouchi et al (2006); Stohl et al (2010); Li et al (2011);and Yao et al (2012). Most recently, Fang et al (2014Fang et al ( , 2015 have provided bottom-up and top-down estimates of HFC-23 emissions from China and East Asia and included observed HFC-23 mixing ratios at three stations -Gosan, South Korea, and Hateruma and Cape Ochi-ishi, Japan.…”
Section: Introductionmentioning
confidence: 99%
“…This feature makes LPDMs very efficient for the purpose of atmospheric inversion and they have been previously used in numerous studies (e.g. Gerbig et al, 2003;Lauvaux et al, 2009;Stohl et al, 2010;Thompson et al, 2011;Keller et al, 2012;Brunner et al, 2012). Lagrangian models may be used on a global scale (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When applying an LPDM for global analysis, a long-term integration is required (see Stohl et al, 2010), although this approach is not as computationally efficient as that of Eulerian models. This problem may be overcome by using a coupled model as the resolution of the flux data for an LPDM can be selected independently from the resolution of the simulation grid for a Eulerian model and its flux data.…”
Section: Introductionmentioning
confidence: 99%
“…Combining Eulerian and Lagrangian models offer the opportunity of constructing a cost-efficient, high-resolution surface flux data assimilation system. The high-resolution Lagrangian model requires just one run for every observation (e.g., Stohl et al, 2010) regardless of number of iterations, whereas the Eulerian component has lower resolution and requires forward and adjoint model runs for every iteration before convergence (Chevallier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%